2012
DOI: 10.1038/bmt.2012.56
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with development of ocular GVHD defined by NIH consensus criteria

Abstract: We studied 172 patients for development of ocular graft-versus-host disease (GVHD) after allogeneic stem cell transplantation (allo-SCT) from 2002 to 2009. Ocular GVHD was diagnosed in 60 patients (38%), with 27 (16%) being diagnosed at days 100 and 33 (23%) beyond day 100 for a 2-year cumulative incidence of 35% (95% confidence interval (CI), 28 --43). The positive and negative predictive values of a Schirmer I test score (using p5 mm as a cutoff) in predicting ocular GVHD (day 100) were 41 and 82%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 34 publications
(23 reference statements)
2
82
4
2
Order By: Relevance
“…Ivanir et al 18 reported that, among the 111 allo-HSCT patients in their study, 28% had high Ocular Surface Disease Index scores, 31% had a very low tear break-up time, 50% had a low Schirmer test score in at least one eye (severe dry eye) and 37% had chronic ocular GVHD. Jacob et al 10 studied 172 patients and analyzed the prevalence of risk factors associated with ocular GVHD as defined by the NIH consensus criteria. Ocular GVHD was diagnosed in 16% at 100 days and 23% at 4100 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ivanir et al 18 reported that, among the 111 allo-HSCT patients in their study, 28% had high Ocular Surface Disease Index scores, 31% had a very low tear break-up time, 50% had a low Schirmer test score in at least one eye (severe dry eye) and 37% had chronic ocular GVHD. Jacob et al 10 studied 172 patients and analyzed the prevalence of risk factors associated with ocular GVHD as defined by the NIH consensus criteria. Ocular GVHD was diagnosed in 16% at 100 days and 23% at 4100 days.…”
Section: Discussionmentioning
confidence: 99%
“…Grading of ocular GVHD was based on the NIH consensus criteria. 9,10 Subjective symptoms, best corrected visual acuity, slit lamp examination, intraocular pressure, Schirmer test results, tear break-up time and fluorescein corneal staining were also examined. Anterior segment photographs were obtained to classify the severity of ocular GVHD ( Figure 1).…”
Section: Clinical Assessments and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditioning was myeoablative in 20% of cases, of reduced intensity in 76% of cases and limited to TBI of 2 Gy (mini-conditioning) in 4% of cases. After aSCT all patients were staged for ocular GvHD in accordance with the National Institutes of Health (NIH) consensus criteria 7,8 on the day of meibography. Further patient characteristics are shown in Tables 1 and 2.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…7 The TFBUT was measured by instilling small amounts of fluorescein into the inferior cul-de-sac. To detect the TFBUT, the cornea was observed with the blue light of a cobalt filter, and the time between the last eyelid blink and the appearance of dark areas on the cornea was measured in seconds.…”
mentioning
confidence: 99%